SHM_415483_HST_3D Thick-Butted Stone Axe - Lernestål, Erik; Bonnevier, Helena; National Historical Museums (National Historical Museums, 2026)
Photogrammetric 3D model of a Middle Neolithic thick-butted stone axe from Skåne, currently held in the collections of the National Historical Museums in Stockholm, Sweden.

Link to the Dynamic Collection platform

https://dyncoll.ht.lu.se/artifact_view.php?item=672

Link to Sök I Samlingarna

https://samlingar.shm.se/object/32C8AAEC-C1E6-4568-8101-1FE718143508
Keywords: 3D Model; Museum Object; Archaeology; Archaeology; Photogrammetry; History and archaeology; Archaeology/history; Dynamic Collections; Swedish Middle Neolithic; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi